Faktor Determinan Kejadian Stunting pada Anak Sekolah dan Pengaruhnya terhadap Prestasi Belajar - Erina Yunita (Universitas Mitra Indonesia, 2020)
AbstractGrowth and development of each child is different, some are fast or slow, because in the process of growth and development there are several aspects that affect, including the talent factor (genetic), environment (nutrition and ways of care), and convergence (a combination of talent and environment ). This study intends to investigate whether the determinants of Stunting events in school children and their effects on learning achievement. The design of this study is analytical research with the Cross Sectional Study design. Measurements were made on the independent variables (mother's education, mother's knowledge, mother's occupation, number of family members, family income and energy consumption and protein of school children) and the dependent variables (stiunting events and learning achievement) at the same time. The population is all children in grades II to VI, SDN 09 Nanggalo, with 332 children. From the results of statistical tests it is known that there is a relationship between student achievement with stunting